Brain morphological analysis in PTEN hamartoma tumor syndrome. Issue 5 (12th March 2020) - Shiohama, Tadashi; Levman, Jacob; Vasung, Lana; Takahashi, Emi
Abstract: PTEN hamartoma tumor syndrome (PHTS) is a spectrum of hereditary cancer syndromes caused by germline mutations in PTEN . PHTS is of high interest, because of its high rate of neurological comorbidities including macrocephaly, autism spectrum disorder, and intellectual dysfunction. Since detailed brain morphology and connectivity of PHTS remain unclear, we quantitatively evaluated brain magnetic resonance imaging (MRI) in PHTS. Sixteen structural T1‐weighted and 9 diffusion‐weighted MR images from 12 PHTS patients and neurotypical controls were used for structural and high‐angular resolution diffusion MRI (HARDI) tractography analyses. Mega‐corpus callosum was observed in 75%, polymicrogyria in 33%, periventricular white matter lesions in 83%, and heterotopia in 17% of the PHTS participants. While gyrification index and hemispheric cortical thickness showed no significant differences between the two groups, significantly increased global and regional brain volumes, and regionally thicker cortices in PHTS participants were observed. HARDI tractography showed increased volume and length of callosal pathways, increased volume of the arcuate fasciculi (AF), and increased length of the bilateral inferior longitudinal fasciculi (ILF), bilateral inferior fronto‐occipital fasciculi (IFOF), and bilateral uncinate fasciculus. A decrease in fractional anisotropy and an increased in apparent diffusion coefficient values of the AF, left ILF, and left IFOF in PHTS.